Role of Vitamin E and the Orexin System in Neuroprotection - Maria Ester La Torre; Ines Villano; Marcellino Monda; Antonietta Messina; Giuseppe Cibelli; Anna Valenzano; Daniela Pisanelli; Maria Antonietta Panaro; Nicola Tartaglia; Antonio Ambrosi; Marco Carotenuto; Vincenzo Monda; et al. (Brain Sciences, 2021)
Microglia are the first line of defense at the level of the central nervous system (CNS). Phenotypic change in microglia can be regulated by various factors, including the orexin system. Neuroinflammation is an inflammatory process mediated by cytokines, by the lack of interaction between neurotransmitters and their specific receptors, caused by systemic tissue damage or, more often, associated with direct damage to the CNS. Chronic activation of microglia could lead to long-term neurodegenerative diseases. This review aims to explore how tocopherol (vitamin E) and the orexin system may play a role in the prevention and treatment of microglia inflammation and, consequently, in neurodegenerative diseases thanks to its antioxidant properties. The results of animal and in vitro studies provide evidence to support the use of tocopherol for a reduction in microglia inflammation as well as a greater activation of the orexinergic system. Although there is much in vivo and in vitro evidence of vitamin E antioxidant and protective abilities, there are still conflicting results for its use as a treatment for neurodegenerative diseases that speculate that vitamin E, under certain conditions or genetic predispositions, can be pro-oxidant and harmful.